Insight Into Microbial Applications for the Biodegradation of Pyrethroid Insecticides - Bhatt, Pankaj; Huang, Yaohua; Zhan, Hui; Chen, Shaohua (Frontiers in Microbiology, 2019)
Pyrethroids are globally used broad spectrum insecticides. Presence of chiral carbon differentiates among various forms of pyrethroids. Microbial approaches have emerged as a popular solution to counter pyrethroid toxicity to marine life and mammals. Bacterial and fungal strains can effectively degrade pyrethroids into non-toxic compounds. Different strains of bacteria and fungi such as Bacillus spp., Psudomonas flourescens, Brevibacterium sp., Acinetobactor sp., Aspergillus sp., Candida sp., Trichoderma sp., and Candia spp, are used for the biodegradation of pyrethroids. Hydrolysis of ester bond by enzyme esterase/carboxyl esterase is the initial step in pyrethroid biodegradation. Esterase is found in bacteria, fungi and mammalian liver microsome cells that indicates its hydrolysis ability in humans and other animals. Biodegradation pattern and detected metabolites reveal the microbial consumption of pyrethroids as carbon and nitrogen source. In this review we aim to explore pyrethroid degrading strains, enzymes and metabolites produced by microbial strains. This review paper covers in-depth knowledge of pyrethroids and recommends possible solutions to minimize their environmental toxicity.